Analisis Rasio Likuiditas, Solvabilitas, Profitabilitas dan Aktivitas untuk Menilai Kinerja Keuangan PT. Ever Shine Tex Tbk - Unknown Author (Realiable Accounting Journal, 2024)
This research aims to analyze, test Liquidity, Solvability, Profitability and Activities to measure the Financial Performance of PT. Ever Shine Tex Tbk from 2019 to 2022. PT. Ever Shine Tex Tbk certainly needs good management from inventory management, funding so that the company can avoid losses experienced for 2 years. The analysis methodology used is the quantitative descriptive analysis method. Data collection techniques with financial report analysis usingdocumentation, in the form of annual reports published via the internet via the sitehttps://www.idx.co.id/id. The results of this research show that PT. Ever Shine Tex Tbk where the liquidity ratio is in a liquid state. Solvency ratios, profitability ratios and activity ratios are in a poor condition because they are below standard financial ratios.